2016
DOI: 10.1002/2015gl067265
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and natural contributions to the Southeast Pacific precipitation decline and recent megadrought in central Chile

Abstract: Within large uncertainties in the precipitation response to greenhouse gas forcing, the Southeast Pacific drying stands out as a robust signature within climate models. A precipitation decline, of consistent direction but of larger amplitude than obtained in simulations with historical climate forcing, has been observed in central Chile since the late 1970s. To attribute the causes of this trend, we analyze local rain gauge data and contrast them to a large ensemble of both fully coupled and sea surface temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
225
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(249 citation statements)
references
References 55 publications
15
225
0
9
Order By: Relevance
“…Estimations of the future runoff trend and melt contribution from Universidad Glacier are beyond the scope of this work. However, the possibility of increased persistence and recurrence of droughts in central Chile (Bosier et al, 2016) would increase the hydrological importance of Universidad Glacier in the future and therefore more research is needed in order to address these issues.…”
Section: Glacier Contribution To Basin Streamflowmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimations of the future runoff trend and melt contribution from Universidad Glacier are beyond the scope of this work. However, the possibility of increased persistence and recurrence of droughts in central Chile (Bosier et al, 2016) would increase the hydrological importance of Universidad Glacier in the future and therefore more research is needed in order to address these issues.…”
Section: Glacier Contribution To Basin Streamflowmentioning
confidence: 99%
“…Hence, glacier runoff becomes critical to maintaining flows in the Tinguiririca River during years when summer drought extends into autumn, e.g. in the period 2010-2015 (Bosier et al, 2016), and in dry winters when snowpack accumulation at highelevation sites is small. Research by Gascoin et al (2011) and Pourrier et al (2014) on glaciers of the arid Andes has revealed the hydrological importance of glaciers to the north of the Tinguiririca Basin.…”
Section: Glacier Contribution To Basin Streamflowmentioning
confidence: 99%
See 1 more Smart Citation
“…These proxy records can provide time series at yearly resolution, capable of delivering historical information on natural variability, estimations of return periods of extreme events such as droughts, and on the correlation with large-scale climatic forcings (Meko and Woodhouse, 2011;Sauchyn et al, 2011). In Chile, dendrohydrology has already been utilized for streamflow reconstruction in four major rivers: Maule (35 (Urrutia et al, 2011)), Biobío (37 (Muñoz et al, 2016)), Puelo (41 (Lara et al, 2008)), and Baker (47 (Lara et al, 2015)). To date, however, these studies have not yet been fully utilized for 5 watershed planning and management.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is need to extend the observational record to better understand longterm (e.g. centuries to millennia) variability and trends in streamflow, thus providing useful information for hydrological assessment of governmental and private planning initiatives within watersheds of SCC (Lara et al, 2015;Muñoz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%